1999
DOI: 10.1364/oe.5.000048
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of chaotic spatiotemporal filamentation in large broad area lasers by spatially structured optical feedback

Abstract: In large high-power broad-area lasers the spatiotemporal filamentation processes and instabilities occur macroscopic as well as on microscopic scales. Numerical simulations on the basis of Maxwell- Bloch equations for large longitudinally and transversely extended semiconductor lasers reveal the internal spatial and temporal processes, providing the relevant scales on which control for stabilization consequently has to occur. It is demonstrated that the combined longitudinal instabilities, filamentation, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 18 publications
0
23
0
Order By: Relevance
“…As a result, the output power of these lasers is severely restricted, limiting their applications. Current approaches for the stabilization of output beam's spatial structure commonly rely on an external forcing techniques such as optical injection [7] and optical feedback in various configurations spatially structured feedback [8,9] and feedback from external cavities [10,11]. All these techniques reduce the main advantage of VCSEL lasers: their compactness, and thus limit their applicability.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the output power of these lasers is severely restricted, limiting their applications. Current approaches for the stabilization of output beam's spatial structure commonly rely on an external forcing techniques such as optical injection [7] and optical feedback in various configurations spatially structured feedback [8,9] and feedback from external cavities [10,11]. All these techniques reduce the main advantage of VCSEL lasers: their compactness, and thus limit their applicability.…”
Section: Introductionmentioning
confidence: 99%
“…of several millimeters, considering the properties of the 1D spatial Fourier-transform, vacuum wavelength 0 , and (effective) refractive index (eff) [9], but for best differential quantum efficiency a semiconductor laser resonator should rather be short [26]. Thus, currently, that is, for this contribution, we have retracted the branches (once more) so that they spatially coincide, giving a compact linear 2f geometry (1f plus the path after reflection, the resonator thus called "retracted twice"), as sketched in Figure 2.…”
Section: Conceptsmentioning
confidence: 99%
“…In most cases either the BAL facets or the lateral (effective) refractive index or pump current distributions are modified [1][2][3][4][5][6][7][8] (if so including transverse Bragg gratings [7,8]) or an external cavity is used [7][8][9][10][11][12][13][14] to achieve the desired transverse mode selection (TMS) (and if applicable also to stabilize a longitudinal mode [7,8]). In all these cases eventually spatial frequency filtering is performed.…”
Section: Introductionmentioning
confidence: 99%
“…The large width of the active region leads to the emission of many transverse modes. Moreover the high BAL power causes strong non-linear optical coupling between the field and the gain medium and results in an uncontrolled filamentation of the gain profile, which destabilizes the transverse modes on a 10 ps time scale [5]. The emission of BALs can be controlled e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The emission of BALs can be controlled e.g. using a grating integrated in the semiconductor chip [2][3][4] or by external cavities [5][6][7][8]. It was found that the feedback strength has a strong influence on the characteristics of the BAL's dynamics.…”
Section: Introductionmentioning
confidence: 99%